Wind/wave interactions in the surf zone - King, Daniel Martin. (1994)
Wind/wave interactions in the surf zone are studied using a wave tank and environmental wind tunnel. The wind simulation is achieved over a relatively short fetch using accelerated growth techniques at a scale of roughly 1:100. Waves are scaled at approximately 1:50, and consequently there is some scaling mis-match between the wind and wave simulations.